Bahan Ajar Menyusun Karya Ilmiah Mahasiswa Bermedia Web - Rifqi Rohmanul Khakim; Dawud Dawud; Titik Harsiati (Pascasarjana Universitas Negeri Malang, 2021)
Abstract: This development research aims to produce teaching material products to compile web-media scientific papers used by students in scientific Indonesian courses in tertiary institutions. The development model used is the ADDIE model which includes analyze, design, development, implementation, and evaluation. The development of teaching materials products takes into account four aspects, namely content / substance, visual appearance (user interface), user experience (user experience), and language. Product assessment was carried out in four groups, namely experts in scientific writing, learning media experts, practitioners, and students. The results of the assessment of the four groups obtained a percentage of 86.6% which stated that the teaching material product was very feasible and ready to be implemented. Abstrak: Penelitian pengembangan ini bertujuan untuk untuk menghasilkan produk bahan ajar menyusun karya ilmiah bermedia web yang digunakan mahasiswa dalam mata kuliah Bahasa Indonesia Keilmuan di Perguruan  Tinggi. Model pengembangan yang digunakan adalah model ADDIE meliputi analyze, design, development, implementation, dan evaluation. Pengembangan produk bahan ajar ini memperhatikan empat aspek, yaitu isi/substansi, tampilan visual (user interface), pengalaman pengguna (user experience), dan bahasa. Penilaian produk dilakukan kepada empat kelompok, yaitu ahli penyusunan karya ilmiah, ahli media pembelajaran, praktisi, dan mahasiswa. Hasil penilaian dari keempat kelompok tersebut mendapatkan persentase sebesar 86,6% yang menyatakan bahwa produk bahan ajar sangat layak dan siap untuk diimplementasikan.